Brief Report: Development of a Robotic Intervention Platform for Young Children with ASD. - Warren, Zachary; Zheng, Zhi; Das, Shuvajit; Young, Eric; Swanson, Amy; Weitlauf, Amy; Sarkar, Nilanjan (Journal of Autism & Developmental Disorders, 2015)
Increasingly researchers are attempting to develop robotic technologies for children with autism spectrum disorder (ASD). This pilot study investigated the development and application of a novel robotic system capable of dynamic, adaptive, and autonomous interaction during imitation tasks with embedded real-time performance evaluation and feedback. The system was designed to incorporate both a humanoid robot and a human examiner. We compared child performance within system across these conditions in a sample of preschool children with ASD (n = 8) and a control sample of typically developing children (n = 8). The system was well-tolerated in the sample, children with ASD exhibited greater attention to the robotic system than the human administrator, and for children with ASD imitation performance appeared superior during the robotic interaction.